Role of Myokines in Myositis Pathogenesis and Their Potential to be New Therapeutic Targets in Idiopathic Inflammatory Myopathies - Vlad Mageriu; Emilia Manole; Alexandra E. Bastian; Florica Staniceanu (Journal of Immunology Research)
Idiopathic inflammatory myopathies (IIM) represent a heterogeneous group of autoimmune diseases whose treatment is often a challenge. Many patients, even after immunosuppressive therapy, do not respond to treatment, so new alternatives have been sought for this. Therefore, other signaling pathways that could contribute to the pathogenesis of myositis have been investigated, such as the expression of myokines in skeletal muscle in response to the inflammatory process. In this review, we will refer to these muscle cytokines that are overexpressed or downregulated in skeletal muscle in patients with various forms of IIM, thus being able to contribute to the maintenance of the autoimmune process. Some muscle cytokines, through their antagonistic action, may be a helpful contributor to the disease modulation, and thus, they could represent personalized treatment targets. Here, we consider the main myokines involved in the pathogenesis of myositis, expressing our view on the possibility of using them as potential therapeutic targets: interleukins IL-6, IL-15, and IL-18; chemokines CXCL10, CCL2, CCL3, CCL4, CCL5, and CCL20; myostatin; follistatin; decorin; osteonectin; and insulin-like 6. An interesting topic regarding the complex connection between myokines and noninflammatory pathways implied in IIM has also been briefly described, because it is an important scientific approach to the pathogenesis of IIM and can be a therapeutic alternative to be considered, especially for the patients who do not respond to immunosuppressive treatment.